Current State and Trends of Openness of the Ukrainian Economy - Ankhelko, Iryna; Lekh, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The essence of openness of the economy as an object of theoretical study based on the analysis of publications and research of domestic and foreign scientists is explored in the article. On that basis, the authors give their interpretation of the concept. It is noted that the consistent expansion of economic openness is an important factor in modern economic development. Four groups of the division of national economies by the criterion of openness, namely by the share of exports in the country's GDP, are considered. The main conditions of an open economy are highlighted and the main tools (economic and political) with which it is possible to achieve the expansion of economic openness are given. An assessment of the current state and trends of openness of the national economy, based on the analysis of the main indicators of exports and imports of goods and services, as well as the geographical structure of Ukraine's foreign trade by recipient countries and donor countries of goods and services, has been made. It was found that in the current conditions of socio-economic instability, the openness of Ukraine’s economy remains at a fairly high level, which causes its close dependence on changes in external conditions. It is analyzed that the lion's share in the overall structure of Ukraine's foreign trade belongs to goods. The principal recipient countries of Ukrainian goods and services and donor countries in 2020 have been identified. The most common goods and services in the structure of exports and imports of Ukraine are also highlighted. In particular, it is noted that the most common goods for export were products of plant origin, base metals and articles base metals, fats and oils of animal or vegetable origin, and among services - transport services. At the same time, it was determined that the highest volume of imports in the general structure of Ukraine's foreign trade was achieved via machinery, equipment and machinery, electrical equipment and transport services import. It is generalized that the openness of Ukraine's economy is essential for its socio-economic development. Importantly to maximise the use of openness advantages that leads to productivity increasing and adaptation of production to growing competition that in turn is an important factor in improving the overall efficiency of the economy. It is recommended for ensuring the economic development of Ukraine, along with the foreign trade component of economic openness, it is also necessary to develop financial (including investment, technological, communicational) and political components.